ANALISIS MATERIAL REMOVAL RATE DAN SURFACE ROUGHNESS PADA PROSES SINKER-EDM MENGGUNAKAN ELEKTRODA TEMBAGA - ANDRI AHMAD SYAHID; GHANY HERYANA; SUKARMAN (Sekolah Tinggi Teknologi Wastukancana, 2022)
Electrical discharge machining (EDM) is one method of manufacturing precise parts with materials that are difficult to cut. EDM has wide applications in the automotive and aerospace industries. The process of electrical erosion consists of the removal of material from the workpiece due to an electric discharge that occurs between the work electrode and the workpiece surface. The electrodes and the workpiece are connected to an electric charge generator.This thesis presents the results of experimental research on electrical discharge machining (EDM), in which the workpiece material is SPHC plate and copper electrodes. The method used in this experiment is the Taguchi method to determine the optimal parameters by varying the current parameters (7A, 12A and 15A), spark on time (210 s, 340 s and 400 s), Gap (50V, 45V and 40V). Process performance measured in this case is the Material Removal Rate and Surface Rougness. The results of the experiment using the Taguchi method showed that the largest optimal MRR was 82.10 mm3/min at current=15 A; Spark on time= 340 s; gap= 50 volts. For the smallest optimal value of SR is 26.00 m at 7 A current; Spark on time= 210 s; gap= 45 volts.